PERTIMBANGAN PELAKU USAHA DALAM MEMILIH LOKASI USAHA DI LOOP GRAHA FAMILI - Lura, Ronald R Konda (Universitas Widya Kartika Surabaya, 2024)
Competition in various business sectors is currently getting tighter. To ensure that the products produced by the company are superior and attractive, the company needs to improve performance in all aspects, especially in the operational field. One of the activities that is directly related to the company's operational activities is the activity to determine the location of the business. Determining the location of the company is certainly a problem that will be faced by every company, where the business or business that is established as an operational place. Therefore, it is necessary to consider or support information for determining the business location before determining the right business location. From this explanation, this study aims to find out the basic considerations in choosing Loop Graha as the location of the business.The research method used in this study is the Descriptive Qualitative method, and the data analysis technique used is Content Analysis, with the number of respondents used being 8 business actors operating in the Graha Famili Loop.The results of this study are business actors who have businesses in the graha loop who are the resource persons in this study, it was found that the selection of business locations is based on strategic considerations such as: location considerations, facility considerations, environmental considerations and traffic considerations